2020
DOI: 10.1126/scisignal.aay6318
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based mechanism of preferential complex formation by apoptosis signal–regulating kinases

Abstract: Apoptosis signal–regulating kinases (ASK1, ASK2, and ASK3) are activators of the p38 and c-Jun N-terminal kinase (JNK) mitogen-activated protein kinase (MAPK) pathways. ASK1–3 form oligomeric complexes known as ASK signalosomes that initiate signaling cascades in response to diverse stress stimuli. Here, we demonstrated that oligomerization of ASK proteins is driven by previously uncharacterized sterile-alpha motif (SAM) domains that reside at the carboxy-terminus of each ASK protein. SAM domains from ASK1–3 e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…S2A): two intrinsically disordered regions (IDRs; Fig. S2B), one coiled-coil domain (CC), one sterile alpha motif domain (SAM) ( 25 ) and one low complexity region (LCR). Between ASK3 CT mutants with these deletions, CTΔCC, CTΔSAM and CTΔLCR exhibited reduced condensation ability compared with the original CT (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S2A): two intrinsically disordered regions (IDRs; Fig. S2B), one coiled-coil domain (CC), one sterile alpha motif domain (SAM) ( 25 ) and one low complexity region (LCR). Between ASK3 CT mutants with these deletions, CTΔCC, CTΔSAM and CTΔLCR exhibited reduced condensation ability compared with the original CT (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…First, we coexpressed the KD of ASK1 with a PKA catalytic subunit, but the KD failed to be activated, whereas full-length ASK1 was activated, suggesting that the N-terminus and/or C-terminus are required for activation (Fig 2D). Next, we focused on the C-terminal region, which harbors a predicted C-terminal coiled-coil (CCC) domain [34] and a sterile-alpha motif (SAM) domain [45], which is essential for high-order oligomerization of ASK1. Interestingly, exogenously expressed PKA did not activate both ⊿C and ⊿CCC of ASK1 (Fig 2E), which indicates that the C-terminal regulatory region, specifically a domain for homo-oligomerization, is a prerequisite for PKA-dependent ASK1 activation.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous analysis, we discovered that ASK1 forms a high molecular mass signaling complex (>MDa, compared to ~150 kDa for the monomer) [53], and subsequent studies have shed light on a wide variety of components of this complex [28,45], including ASK2, a member of the ASK family. ASK2 tightly forms a heteromeric complex with ASK1 and supports ASK1 kinase activity [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The apoptosis signal-regulating kinase (ASK) family, which consists of ASK1, ASK2, and ASK3, is a member of MAP3K and shares similar amino acid sequences throughout the kinase domain but functions differently in many cases [ 22 24 ]. Additionally, ASKs can form heteromeric complexes and are mutually interactive in some cases [ 25 28 ]. Although the key role of ASK1 is cell death regulation [ 29 33 ], we previously reported that ASK1 also functions as a differentiation regulator through gene induction in immature brown adipocytes and contributes to functional maturation [ 9 ].…”
Section: Introductionmentioning
confidence: 99%